Maximum influence : the 12 universal laws of power persuasion - Mortensen, Kurt W. (AMACOM, American Management Association, 2013)
Salespeople, consultants, managers, executives, entrepreneurs. . . Influence is a crucial tool for absolutely anyone seeking success and prosperity. But how can everyday people actually become more influential? Maximum Influence unlocks the secrets of the master influencers. Now in an all-new edition, the book combines scientific research with real-world studies, presenting the most authoritative and effective arsenal of persuasion techniques ever. Author and renowned expert Kurt Mortensen reveals the 12 Laws of Persuasion, explaining why each law works, how to use it, and what to avoid. You will learn about the law of dissonance, the law of contrast, the law of expectation-and nine other proven principles that consciously and unconsciously propel people to act. You willalso discover how to: - Read anyone instantly - Get people to trust you instinctively - Change minds easily - And convince anyone to give you almost anything. With new case studies and cutting-edge influencing techniques, this is the ultimate guide to the art and science of getting exactly what you want-when you want.